Structural stability of the hepatitis C model with the proliferation of infected and uninfected hepatocytes - Z. Navickas; R. Marcinkevicius; I. Telksniene; T. Telksnys; M. Ragulskis (Mathematical and Computer Modelling of Dynamical Systems, 2024)
The structural stability of the hepatitis C model with the proliferation of infected and uninfected hepatocytes is investigated in this paper. The model is clinically verified to accurately reflect the viral dynamics of hepatitis C. It is demonstrated that the limit transition from the hepatitis C model to the Riccati system coupled with the diffusive terms leads to the elimination of the quadratic terms. Such a novel effect leads to the introduction of the concept of the deformed order-1 solitary solutions. The generalized operator of differentiation is used to construct the deformed order-1 solitary solutions to the Riccati system coupled with the diffusive terms. Finally, it is demonstrated that the Riccati system coupled with the diffusive terms admits non-deformed order-1 solitary solutions, which proves the structural instability of the hepatitis C model with the proliferation of infected and uninfected hepatocytes.